ATTEMPTS TO EXPLAIN THE “ASIA’S MIRACLE” BY FACTOR THEORY. THE ROLE OF EDUCATIONAL EXPENSES - N. F. Ugaslov (Russian Journal of Economics and Law, 2013)
Objective: to reveal the limits of human capital growth in developing and transitive economies. Method: comparative analysis. Results: hypothesis of formulated, that educational expenses under the average per capita GDP lower than $ 10 thousand can not significantly influence the growth of educational index of the population and the growth of human capital. Scientific novelty: the influence of GDP growth on investment level in science and education in developing countries is revealed; it is shown that reducing costs on education increases the Russia’ lagging behind the West, and that with the per capita GDP existing in Russia and Third World countries the effect of education financing of less than 7% will be negligible. Practical value: possibility to use the research results when investing capital into science and education in Russia.